1984
DOI: 10.1021/bi00303a013
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids chiral at phosphorus. Absolute configuration of chiral thiophospholipids and stereospecificity of phospholipase D

Abstract: Separate diastereomers of 1,2-dipalmitoyl-sn-glycero-3- thiophosphoethanolamine ( DPPsE ) were prepared in 97% diastereomeric purity and characterized by 31P, 13C, and 1H nuclear magnetic resonance (NMR). The isomers hydrolyzed by phospholipases A2 and C specifically were designated as isomer B (31P NMR delta 59.13 in CDCl3 + Et3N ) and isomer A (59.29 ppm), respectively, analogous to the isomers B and A of 1,2-dipalmitoyl-sn-glycero-3- thiophosphocholine ( DPPsC ) [ Bruzik , K., Jiang , R.-T., & Tsai, M.-D. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Tsai and coworkers who synthesized chiral nucleotides, in which a P‐O bond was substituted by P‐S or P‐O‐isotopes ( 17 O or 18 O). These stereochemically defined phospholipids were found to be useful in studies of the stereochemical mechanisms of reactions catalyzed by phospholipase A 2 [34,35] and the formation of inositol 1‐phosphate catalyzed by phospholipase C [36]. In the present work, we describe, for the first time, preparation of chiral phospholipids PL1 Ac,Me and PL2 Ac,Me by derivatization of two natural prochiral phospholipids PL1 and PL2, which were synthesized by the novel glycosyltransferase from S. aureus expressed in E. coli BL21 (DE3).…”
Section: Discussionmentioning
confidence: 99%
“…Tsai and coworkers who synthesized chiral nucleotides, in which a P‐O bond was substituted by P‐S or P‐O‐isotopes ( 17 O or 18 O). These stereochemically defined phospholipids were found to be useful in studies of the stereochemical mechanisms of reactions catalyzed by phospholipase A 2 [34,35] and the formation of inositol 1‐phosphate catalyzed by phospholipase C [36]. In the present work, we describe, for the first time, preparation of chiral phospholipids PL1 Ac,Me and PL2 Ac,Me by derivatization of two natural prochiral phospholipids PL1 and PL2, which were synthesized by the novel glycosyltransferase from S. aureus expressed in E. coli BL21 (DE3).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies using strategically radiolabeled substrates and intermediates suggested that PLD enzymes use a two-step "ping pong" reaction mechanism in which a covalent phosphoenzyme intermediate is created before release of the product (Stanacev and Stuhne-Sekalec, 1970;Jiang et al, 1984). This reaction mechanism was supported by structural studies using Yersinia pestis murine toxin (Rudolph et al, 1999) and Nuc endonuclease (Gottlin et al, 1998), both members of the HKDcontaining PLD superfamily.…”
Section: A Structure and Mechanismmentioning
confidence: 99%
“…Other studies indicated that PLD from cabbage retained the configuration of the phosphorus atom in both the hydrolysis and in the transphosphatidylation reaction with different radioactively labelled substrates, all having a chiral phosphorus atom. 5,6,7 In a recent paper, a comparison between PLD activity from two Streptomyces species is presented. 8 Interestingly, one of these PLD enzymes possesses neither of the above-mentioned HxK(x) 4 D (HKD) sequence repeats, resulting in an apparently altered reaction mechanism, which does not proceed through a covalent enzyme -substrate intermediate.…”
Section: Introductionmentioning
confidence: 99%